Slot‐Die‐Printed Electroactive Polymer Actuators with High‐Strain Sensitivity for Soft Robotic Applications - Duanhao Lu; Ying Yu; Yuxin Zuo; Yong Lv; Tianyu Zhang; You Li; Zhangfeng Zhao (Macromolecular Materials and Engineering)
Abstract Ionic electroactive polymer gels are widely employed as actuators in soft robotics due to their ability to undergo rapid mechanical deformation under low‐voltage. How to improve the performance of the ionic electroactive polymer actuators is always the focus of research in this field. Optimizing the migration of ions within the actuator is crucial for enhancing the actuation performance. In this regard, this study innovatively introduces slot‐die‐printing technology to fabricate gel actuation layers characterized by high smoothness and uniform particle distribution, achieving seamless integration between the electrodes and gel actuation layers, while mitigating issues associated with ion accumulation due to polymer clustering. Furthermore, this study attempts to add lactic acid to the traditional CS‐PVA‐IL gel, effectively strengthening the connection between CS and PVA, and promoting smooth ion transport within the gel. The results demonstrate that the actuators prepared in this study achieved a high‐bending‐strain of 0.35%, with a retention rate of 91% for actuation displacement after 10 000 cycles, showcasing superior actuation performance compared to existing research. The fabrication method proposed in this study is simple and highly reproducible, making it suitable for widespread industrial application, and providing a new approach for future industrial production of soft robotics.